Obesity Exacerbates Irritable Bowel Syndrome-Related Sleep and Psychiatric Disorders in Women With Polycystic Ovary Syndrome - Tseng, Ping-Huei; Chiu, Han-Mo; Tu, Chia-Hung; Wu, Ming-Shiang; Ho, Hong-Nerng; Chen, Mei-Jou (Frontiers in Endocrinology, 2021)
Background/Objectives: Polycystic ovary syndrome (PCOS) and irritable bowel syndrome (IBS) share similar clinical and psychosocial features. We aimed to investigate the clinical characteristics of IBS in women with PCOS, and its relationship with obesity, metabolic and hormonal profiles, as well as sleep and psychiatric disorders. Subjects/Methods: This is a cross-sectional case-control study of 431 untreated women with PCOS and 259 healthy volunteers. All participants were assessed with a comprehensive clinical evaluation and two questionnaires: the Athens Insomnia Scale (AIS) and the Brief Symptom Rating Scale (BSRS-5). IBS was diagnosed using the Rome III criteria. Obesity was defined as a BMI ≥30 kg/m2. Anthropometric measurements, metabolic, hormonal profiles, and psychosocial morbidities were compared. Results: Women with PCOS were more likely to have IBS (10.7% vs 5.8%, p=0.029) and obesity (29% vs 4%, p<0.001) than healthy volunteers. Mixed-type IBS (IBS-M) was the most common subtype (74%) among patients with PCOS and IBS. There was a higher prevalence of psychiatric morbidities (total BSRS-5 score ≥10) in women with PCOS than in healthy women (11.4% vs 3.5%, p<0.001). Women with PCOS and IBS were more likely to have sleep difficulties (67.4% vs 30.9%, p<0.001) and psychiatric morbidities (21.7% vs 10.1%, p=0.019) than those without IBS. Among women with PCOS, those with both IBS and obesity had the highest risk of developing sleep difficulties (odds ratio: 5.91; 95% confidence interval: 1.77–19.77) and psychiatric distress (odds ratio: 4.39; 95% confidence interval: 1.26–15.29) than those without. Conclusion: Women with PCOS have increased IBS, obesity, sleep and psychiatric disturbances. The presence of IBS in PCOS women is associated with sleep and psychiatric disorders. The coexistence of obesity and IBS exacerbates sleep difficulties and psychiatric distress. Screening and management of IBS and obesity might be warranted to improve sleep and psychiatric disturbances in women with PCOS.